Poetry in the time of pandemic: the therapeutic functionality of Covid Poetry in Corneluis Eady's "Corona Diary" and Julia Alvarez's "How will this pandemic affect poetry?" - Farouk Fouad, Jehan; Sayed Hanafy, Marwa (Journal of poetry therapy, 2025)
The outbreak of the Covid-19 pandemic with its preventive measures has resulted in an ultimate state of alienation. The process of creativity witnessed a transformation and the rise of new writings that voice the writers' inner feelings of alienation and loss of meaning which is obvious in the rise of the Covid poetry. The poems "Corona Diary" by Corneluis Eady and "How Will This Pandemic Affect Poetry?" by Julia Alvarez express that state of alienation and will be explored through the framework of scriptotherapy and Wong's theory of dualism and Meaning Therapy. These poems highlight the centrality of the poem as an alternative space for bringing poets and their audience together and shed light on the novel functionality of poetry as a genre which lends immediacy of expression that parallels the occurrence of the pandemic together with its therapeutic tendencies to heal.